Preparation method of high-selectivity nanofiltration membrane based on functionalized two-dimensional material
By uniformly loading carboxylated molybdenum disulfide nanosheets on the nanofiltration membrane and performing specific treatment, the problem of insufficient selection performance of the molybdenum disulfide composite nanofiltration membrane for inorganic salt ion is solved, and high selectivity and good permeability are achieved. Take into account both.
Patent Information
- Application Number
- CN202411294062.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2024-12-17
AI Technical Summary
While ensuring permeability, the existing molybdenum disulfide composite nanofiltration membrane lacks the selection performance of inorganic salt ions, making it difficult to effectively separate different inorganic salt ions.
By uniformly loading the carboxylated molybdenum disulfide nanosheets onto the separation layer of the nanofiltration membrane, ultrasonic peeling, freeze-drying and stirring treatment, combining the interfacial polymerization reaction of aqueous phase and organic phase monomers, a highly selective nano-produced The filter membrane enhances the unit charge density and electrical strength of the membrane and improves the selection performance of salt ions.
The selection performance of nanofiltration membrane for inorganic salt ions is significantly improved, while maintaining a high permeability, improving the retention rate of different inorganic salt ions.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of nanofiltration membranes, and in particular to a method for preparing a high-selectivity nanofiltration membrane based on functionalized two-dimensional materials. Background Art
[0002] Nanofiltration membrane technology has been widely used in the selective separation of various saline wastewaters due to its excellent selective separation ability. However, due to the "trade-off" effect, the water flux performance of nanofiltration membranes with high selectivity is usually poor. Therefore, how to prepare nanofiltration membranes with both permeability and selectivity remains the focus of research in the field of nanofiltration membrane separation. With the vigorous development of nanoscience, accompanied by the advent of nanomaterials with ideal pore size, excellent chemical resistance, sufficient mechanical strength and excellent antifouling properties, people have paid great attention to the application of thin film nanocomposites in nanofiltration membranes. Molybdenum disulfide (MoS2), as a typical two-dimensional nanomaterial, has been widely used in the field of nanofiltration membrane separation in recent years. Its inherent defects and smooth nano-confined channels between nanosheets are conducive to improving the permeability of nanofiltration membranes.
[0003] Related studies have shown that although the MoS2 composite nanofiltration membrane has good permeability, its ion selectivity is poor. Therefore, how to ensure the permeability of the MoS2 composite nanofiltration membrane while further improving its selectivity for different inorganic salt ions is a key problem and technical barrier that needs to be broken through in this field.
[0004] Therefore, on the basis of loaded molybdenum disulfide material, a technology and membrane preparation method are provided which can significantly improve the selectivity of the membrane for inorganic salt ions while ensuring the membrane permeability, which is of great application value and research significance. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention provides a method for preparing a highly selective nanofiltration membrane based on functionalized two-dimensional materials. Through a special membrane making process, carboxylated molybdenum disulfide nanosheets with excellent dispersibility are uniformly loaded in the separation layer of the nanofiltration membrane, thereby preparing a highly selective nanofiltration membrane without affecting the membrane permeability.
[0006] The present invention discloses a method for preparing a highly selective nanofiltration membrane based on functionalized two-dimensional materials, comprising:
[0007] Step 1: exfoliating and freeze-drying the chemically grafted carboxylated molybdenum disulfide powder to obtain carboxylated molybdenum disulfide nanosheets with excellent dispersibility; preparing an aqueous solution of a preset concentration of the carboxylated molybdenum disulfide nanosheets, stirring and treating the solution as a material dispersion;
[0008] Step 2, piperazine (PIP) is used as an aqueous phase monomer to prepare an aqueous solution as an aqueous phase solution. At the same time, n-hexane is used as a solvent and trimesoyl chloride (TMC) is used as an organic phase solute to prepare a mixed solution as an organic phase solution;
[0009] Step 3: Select a polyethersulfone (PES) ultrafiltration membrane as a base membrane. First, immerse the base membrane in the material dispersion liquid, take it out and place it in a culture dish covered with absorbent paper, and dry the surface after evenly dispersing it.
[0010] Step 4: After the membrane surface is dried, it is immersed in an aqueous solution, taken out and air-dried, and then immersed in an organic solution, taken out again and air-dried, and then heat-cured to obtain a composite nanofiltration membrane with high surface charge density and high selectivity.
[0011] As a further improvement of the present invention, in step 1, the chemical grafting method of the carboxylated molybdenum disulfide powder is a hydrothermal synthesis method, and the reagents used are sodium molybdate, thiourea and thioglycolic acid. The hydrothermal synthesis is carried out at a concentration ratio of 1:2:0.05 at 200-240°C (preferably 220°C) for 30-48h to obtain a carboxylated molybdenum disulfide aqueous solution.
[0012] As a further improvement of the present invention, in step 1, the exfoliation is carried out by ultrasonic dispersion and exfoliation of the carboxylated molybdenum disulfide aqueous solution obtained by hydrothermal synthesis using an ultrasonic cell disruptor to obtain carboxylated molybdenum disulfide nanosheets uniformly dispersed in water, and the ultrasonic conditions are: ultrasonic frequency of 60-80KHz, time of 3-6h, and temperature of 25-30°C.
[0013] As a further improvement of the present invention, in step 1, freeze drying is to freeze dry the peeled carboxylated molybdenum disulfide nanosheet aqueous solution using a freeze dryer to obtain a dry carboxylated molybdenum disulfide nanosheet solid powder, and the freeze drying conditions are: air pressure less than 15Pa, temperature less than -60°C, and time for 36-48h.
[0014] As a further improvement of the present invention, in step 1, the concentration of carboxylated molybdenum disulfide in the preset concentration aqueous solution is 100-300 mg / L.
[0015] As a further improvement of the present invention, in step 1, the stirring treatment is to further disperse the configured carboxylated molybdenum disulfide nanosheet dispersion (aqueous solution of preset concentration) by a magnetic stirrer before use to ensure that the carboxylated molybdenum disulfide nanosheets in the solution are more evenly dispersed when used. The stirring treatment conditions are: the magnetic stirrer speed is 800-1200rpm, and the stirring time is 30-60min.
[0016] As a further improvement of the present invention, in step 2, the concentration of piperazine in the aqueous phase solution is 0.1-0.25 wv%, and the concentration of trimesoyl chloride in the organic phase solution is 0.05-0.15 wv%.
[0017] As a further improvement of the present invention, in step 3, a polyethersulfone (PES) ultrafiltration membrane is selected as the base membrane, and the molecular weight cutoff of the selected base membrane is 80-100 KDa and the size is 7×7 cm.
[0018] As a further improvement of the present invention, in step 3, the base film is immersed in the material dispersion liquid, and the immersion conditions are: temperature of 23-25° C., time of 3-10 min, preferably 5 min.
[0019] As a further improvement of the present invention, in step 3, the uniform dispersion treatment refers to placing the base film taken out from the material dispersion in a culture dish covered with absorbent paper, fixing it in the culture dish with a phoenix clip, and then placing it flat on a constant temperature shaker for mixing and shaking, so that the loaded material on the surface of the membrane is evenly dispersed on the entire membrane surface, and the mixing conditions are: temperature of 25-30°C, amplitude of 1-5mm, preferably amplitude of 3mm, rotation speed of 5-10rpm, time of 3-5min.
[0020] As a further improvement of the present invention, in step 3, surface drying refers to air-drying the membrane surface with a small electric fan, and the air-drying conditions are: the fan power is 25-50W, and the time is 3-5min.
[0021] As a further improvement of the present invention, in step 4,
[0022] The conditions for soaking in the aqueous solution are: temperature of 23-25°C, time of 3-10 min, preferably 5 min;
[0023] The conditions for immersing in the organic phase solution to complete the interfacial polymerization reaction are: temperature 23-25°C, time 30-60s;
[0024] Thermal curing treatment means that the film taken out from the organic phase solution is air-dried, placed in a clean culture dish, and then placed in an oven for drying. The thermal curing conditions (drying conditions) are: temperature of 50-70°C, preferably 60°C, time of 40-80s, preferably 60s. Compared with the prior art, the beneficial effects of the present invention are:
[0025] The present invention performs a pretreatment method of "ultrasonic peeling + freeze drying + stirring" on carboxylated molybdenum disulfide before membrane preparation, so that the carboxylated molybdenum disulfide nanosheets are better dispersed in water, so that they are better loaded on the membrane surface, the loading rate of the functionalized two-dimensional material is increased, the loading effect is greatly improved, and the influence of the carboxyl group on the membrane performance is enhanced;
[0026] The present invention immerses the base film in a dispersion of carboxylated molybdenum disulfide nanosheets before immersing the base film in an aqueous phase and an organic phase, and performs a mixing and shaking treatment after immersion, so that the carboxylated molybdenum disulfide nanosheets are more evenly distributed on the surface of the film, and the contact area between the carboxylated molybdenum disulfide and the aqueous phase and the organic phase monomers is also increased, so as to avoid the formation of agglomeration and cause an uneven film structure;
[0027] The present invention prepares a composite nanofiltration membrane based on carboxylated molybdenum disulfide. The carboxyl group, as a hydrophilic group, not only enhances the hydrophilicity of the membrane, but also, due to its own electrical properties, easily generates unique dipole bonds and π-π bond interactions with salt ions, thereby greatly improving the unit charge density and electrical strength of the membrane surface. In addition, the interlayer nano-confined transmission channel constructed by combining molybdenum disulfide nanosheets is combined, so that the present invention significantly enhances the selectivity of the nanofiltration membrane for salt ions while maintaining a certain permeability of the membrane. DETAILED DESCRIPTION
[0028] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention is clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] Embodiment 1:
[0030] The present invention provides a method for preparing a highly selective nanofiltration membrane based on a functionalized two-dimensional material, and the specific steps are as follows (the following steps without temperature indication are all performed at room temperature):
[0031] S11, immersing molybdenum disulfide in a reagent formed by sodium molybdate, thiourea and thioglycolic acid, and performing hydrothermal synthesis at 220° C. for 36 hours according to a concentration ratio of 1:2:0.05 to obtain a carboxylated molybdenum disulfide aqueous solution;
[0032] S12, using an ultrasonic cell disruptor to perform ultrasonic dispersion and exfoliation of the carboxylated molybdenum disulfide aqueous solution obtained by hydrothermal synthesis at an ultrasonic frequency of 80 KHz for 6 hours;
[0033] S13, using a freeze dryer under vacuum conditions (air pressure less than 15 Pa, temperature less than -60 ° C), the peeled carboxylated molybdenum disulfide nanosheet aqueous solution is freeze-dried for 48 hours to obtain a dry carboxylated molybdenum disulfide nanosheet solid powder;
[0034] S14, taking 100 mg of carboxylated molybdenum disulfide and putting it into 1000 ml of deionized water to prepare an aqueous solution, and stirring it with a magnetic stirrer at a speed of 1200 rpm for 45 minutes to obtain a material dispersion;
[0035] S15, taking a certain amount of piperazine and putting it into a beaker, adding deionized water to prepare an aqueous phase solution with a concentration of 0.1wv%; taking a certain amount of trimesoyl chloride and putting it into a beaker, adding n-hexane to prepare an organic phase solution with a concentration of 0.1wv%;
[0036] S16, cutting a plurality of polyethersulfone (PES) ultrafiltration membranes with a size of 7×7 cm and a molecular weight cutoff of 100 KDa as base membranes for subsequent use;
[0037] S17, soaking the PES base film in the material dispersion and taking it out after 5 minutes;
[0038] S18. Place the membrane taken out from the material dispersion in a culture dish covered with absorbent paper, fix it in the culture dish with a phoenix clip, and place it flat on a constant temperature shaker. At 30°C, set the shaker amplitude to 3 mm and the speed to 10 rpm, and shake for 5 minutes to mix and evenly mix.
[0039] S19, after the mixing is completed, the membrane is taken out and the membrane surface is air-dried for 5 minutes using a small electric fan with a power of 25-50W until the membrane surface is dry;
[0040] S110, immersing the membrane in the aqueous solution for 5 minutes, taking it out, and air-drying it until the membrane surface is dry;
[0041] S111, the membrane after the water phase is dried is further placed into the organic phase solution for interfacial polymerization reaction, taken out after 60 seconds, and air-dried until the membrane surface is dry;
[0042] S112, placing the membrane after re-drying in a 60°C constant temperature drying oven for heat curing, obtaining a highly selective nanofiltration membrane after 60 seconds, taking out the dried highly selective nanofiltration membrane, and sealing it in a water environment for subsequent measurements.
[0043] S113. Take out the dried high permeability nanofiltration membrane, pre-press it at a pressure of 0.6 MPa for 30 minutes, and then test the performance of the prepared high selectivity nanofiltration membrane using pure water, 2000 ppm Na2SO4 aqueous solution, 2000 ppm MgSO4 aqueous solution, 2000 ppm MgCl2 aqueous solution and 2000 ppm NaCl aqueous solution at a pressure of 0.2 MPa.
[0044] The test results show that the pure water permeability of the highly selective nanofiltration membrane is 40.64 L·m -2 ·h -1bar -1 The retention rate of Na2SO4 aqueous solution is 97.97%, the retention rate of MgSO4 aqueous solution is 90.35%, the retention rate of MgCl2 aqueous solution is 77.22%, and the retention rate of NaCl aqueous solution is 45.32%.
[0045] Embodiment 2:
[0046] The present invention provides a method for preparing a highly selective nanofiltration membrane based on a functionalized two-dimensional material, and the specific steps are as follows (the following steps without temperature indication are all performed at room temperature):
[0047] S21, immersing molybdenum disulfide in a reagent formed by sodium molybdate, thiourea and thioglycolic acid, and performing hydrothermal synthesis at 220° C. for 36 hours according to a concentration ratio of 1:2:0.05 to obtain a carboxylated molybdenum disulfide aqueous solution;
[0048] S22, using an ultrasonic cell disruptor to perform ultrasonic dispersion and exfoliation of the carboxylated molybdenum disulfide aqueous solution obtained by hydrothermal synthesis at an ultrasonic frequency of 80 KHz for 6 hours;
[0049] S23, using a freeze dryer under vacuum conditions (air pressure less than 15 Pa, temperature less than -60 ° C), the peeled carboxylated molybdenum disulfide nanosheet aqueous solution is freeze-dried for 48 hours to obtain a dry carboxylated molybdenum disulfide nanosheet solid powder;
[0050] S24, taking 200 mg of carboxylated molybdenum disulfide and putting it into 1000 ml of deionized water to prepare an aqueous solution, and stirring it with a magnetic stirrer at a speed of 1200 rpm for 45 minutes to obtain a material dispersion;
[0051] S25, taking a certain amount of piperazine and putting it into a beaker, adding deionized water to prepare an aqueous phase solution with a concentration of 0.1wv%; taking a certain amount of trimesoyl chloride and putting it into a beaker, adding n-hexane to prepare an organic phase solution with a concentration of 0.1wv%;
[0052] S26, cutting a plurality of polyethersulfone (PES) ultrafiltration membranes with a size of 7×7 cm and a molecular weight cutoff of 100 KDa as base membranes for subsequent use;
[0053] S27, soaking the PES base film in the material dispersion and taking it out after 5 minutes;
[0054] S28. Place the membrane taken out from the material dispersion in a culture dish covered with absorbent paper, fix it in the culture dish with a phoenix clip, and place it flat on a constant temperature shaker. At 30°C, set the shaker amplitude to 3 mm and the speed to 10 rpm, and shake for 5 minutes to mix and evenly mix.
[0055] S29, after the mixing is completed, the membrane is taken out and the membrane surface is air-dried for 5 minutes using a small electric fan with a power of 25-50W until the membrane surface is dry;
[0056] S210, immersing the membrane in the aqueous solution for 5 minutes, taking it out, and air-drying it until the membrane surface is dry;
[0057] S211, the membrane after the water phase is dried is further placed into the organic phase solution for interfacial polymerization reaction, taken out after 60 seconds, and air-dried until the membrane surface is dry;
[0058] S212. The membrane after being dried again is placed in a 60°C constant temperature drying oven for heat curing. After 60 seconds, a highly selective nanofiltration membrane is obtained. The dried highly selective nanofiltration membrane is taken out and sealed in a water environment for subsequent measurements.
[0059] S213. Take out the dried high permeability nanofiltration membrane, pre-press it at a pressure of 0.6 MPa for 30 minutes, and then test the performance of the prepared high selectivity nanofiltration membrane using pure water, 2000 ppm Na2SO4 aqueous solution, 2000 ppm MgSO4 aqueous solution, 2000 ppm MgCl2 aqueous solution and 2000 ppm NaCl aqueous solution at a pressure of 0.2 MPa.
[0060] The test results show that the pure water permeability of the highly selective nanofiltration membrane is 45.19 L·m -2 ·h -1 bar -1 The retention rate of Na2SO4 aqueous solution is 98.08%, the retention rate of MgSO4 aqueous solution is 92.64%, the retention rate of MgCl2 aqueous solution is 81.39%, and the retention rate of NaCl aqueous solution is 47.61%.
[0061] Embodiment 3:
[0062] The present invention provides a method for preparing a highly selective nanofiltration membrane based on a functionalized two-dimensional material, and the specific steps are as follows (the following steps without temperature indication are all performed at room temperature):
[0063] S31, immersing molybdenum disulfide in a reagent formed by sodium molybdate, thiourea and thioglycolic acid, and performing hydrothermal synthesis at 220° C. for 36 hours according to a concentration ratio of 1:2:0.05 to obtain a carboxylated molybdenum disulfide aqueous solution;
[0064] S32, using an ultrasonic cell disruptor to perform ultrasonic dispersion and exfoliation of the carboxylated molybdenum disulfide aqueous solution obtained by hydrothermal synthesis at an ultrasonic frequency of 80 KHz for 6 hours;
[0065] S33, using a freeze dryer under vacuum conditions (air pressure less than 15 Pa, temperature less than -60 ° C), the peeled carboxylated molybdenum disulfide nanosheet aqueous solution is freeze-dried for 48 hours to obtain a dry carboxylated molybdenum disulfide nanosheet solid powder;
[0066] S34, taking 300 mg of carboxylated molybdenum disulfide and putting it into 1000 ml of deionized water to prepare an aqueous solution, and stirring it with a magnetic stirrer at a speed of 1200 rpm for 45 minutes to obtain a material dispersion;
[0067] S35, taking a certain amount of piperazine and putting it into a beaker, adding deionized water to prepare an aqueous phase solution with a concentration of 0.1wv%; taking a certain amount of trimesoyl chloride and putting it into a beaker, adding n-hexane to prepare an organic phase solution with a concentration of 0.1wv%;
[0068] S36, cutting out a plurality of polyethersulfone (PES) ultrafiltration membranes with a size of 7×7 cm and a molecular weight cutoff of 100 KDa as base membranes for subsequent use;
[0069] S37, soaking the PES base film in the material dispersion and taking it out after 5 minutes;
[0070] S38. Place the membrane taken out from the material dispersion in a culture dish covered with absorbent paper, fix it in the culture dish with a phoenix clip, and place it flat on a constant temperature shaker. At 30°C, set the shaker amplitude to 3 mm and the speed to 10 rpm, and shake for 5 minutes to mix and evenly mix.
[0071] S39, after the mixing is completed, the membrane is taken out and the membrane surface is air-dried for 5 minutes using a small electric fan with a power of 25-50W until the membrane surface is dry;
[0072] S310, immersing the membrane in the aqueous solution for 5 minutes, taking it out, and air-drying it until the membrane surface is dry;
[0073] S311, the membrane after the water phase is dried is further placed into the organic phase solution for interfacial polymerization reaction, taken out after 60 seconds, and air-dried until the membrane surface is dry;
[0074] S312, placing the membrane after re-drying in a 60°C constant temperature drying oven for heat curing, obtaining a highly selective nanofiltration membrane after 60 seconds, taking out the dried highly selective nanofiltration membrane, and sealing it in a water environment for subsequent measurements.
[0075] S313. Take out the dried high permeability nanofiltration membrane, pre-press it at a pressure of 0.6 MPa for 30 minutes, and then test the performance of the prepared high selectivity nanofiltration membrane using pure water, 2000 ppm Na2SO4 aqueous solution, 2000 ppm MgSO4 aqueous solution, 2000 ppm MgCl2 aqueous solution and 2000 ppm NaCl aqueous solution at a pressure of 0.2 MPa.
[0076] The test results show that the pure water permeability of the highly selective nanofiltration membrane is 46.75 L·m -2 ·h -1 bar -1 The retention rate of Na2SO4 aqueous solution is 96.24%, the retention rate of MgSO4 aqueous solution is 90.98%, the retention rate of MgCl2 aqueous solution is 79.45%, and the retention rate of NaCl aqueous solution is 41.39%.
[0077] Comparative Example 1
[0078] A nanofiltration membrane was prepared according to the method of Example 1, except that in step 3, 100 mg of molybdenum disulfide (non-functionalized) was put into 1000 ml of deionized water to prepare an aqueous solution, and a magnetic stirrer was used to stir for 45 minutes at a speed of 1200 rpm to obtain a material dispersion.
[0079] The nanofiltration membrane prepared in Comparative Example 1 was tested for performance in the same manner as in Example 1. The test results showed that the pure water permeability of the nanofiltration membrane prepared in Comparative Example 1 was 40.51 L·m -2 ·h -1 bar -1 The retention rate of Na2SO4 aqueous solution is 88.31%, the retention rate of MgSO4 aqueous solution is 80.56%, the retention rate of MgCl2 aqueous solution is 61.34%, and the retention rate of NaCl aqueous solution is 19.17%.
[0080] Comparative Example 2
[0081] The nanofiltration membrane was prepared according to the method of Example 2, except that in step 3, 200 mg of molybdenum disulfide (non-functionalized) was put into 1000 ml of deionized water to prepare an aqueous solution, and a magnetic stirrer was used to stir for 45 minutes at a speed of 1200 rpm to obtain a material dispersion.
[0082] The nanofiltration membrane prepared in Comparative Example 1 was tested for performance in the same manner as in Example 2. The test results showed that the pure water permeability of the nanofiltration membrane prepared in Comparative Example 2 was 44.81 L·m -2 ·h -1 bar -1The retention rate of Na2SO4 aqueous solution is 78.35%, the retention rate of MgSO4 aqueous solution is 75.97%, the retention rate of MgCl2 aqueous solution is 58.12%, and the retention rate of NaCl aqueous solution is 18.66%.
[0083] Comparative Example 3
[0084] The nanofiltration membrane was prepared according to the method of Example 3, except that in step 3, 300 mg of molybdenum disulfide (non-functionalized) was put into 1000 ml of deionized water to prepare an aqueous solution, and a magnetic stirrer was used to stir for 45 minutes at a speed of 1200 rpm to obtain a material dispersion.
[0085] The nanofiltration membrane prepared in Comparative Example 1 was tested for performance in the same manner as in Example 3. The test results showed that the pure water permeability of the nanofiltration membrane prepared in Comparative Example 3 was 47.01 L·m -2 ·h -1 bar -1 The retention rate of Na2SO4 aqueous solution is 76.18%, the retention rate of MgSO4 aqueous solution is 71.36%, the retention rate of MgCl2 aqueous solution is 53.22%, and the retention rate of NaCl aqueous solution is 15.51%.
[0086] Comparative Example 4
[0087] A method for preparing a nanofiltration membrane, the specific steps are as follows (the following steps without temperature indication are all carried out at room temperature):
[0088] S41, taking a certain amount of piperazine and putting it into a beaker, adding deionized water to prepare an aqueous phase solution with a concentration of 0.1wv%; taking a certain amount of trimesoyl chloride and putting it into a beaker, adding n-hexane to prepare an organic phase solution with a concentration of 0.1wv%;
[0089] S42, cutting out a plurality of polyethersulfone (PES) ultrafiltration membranes with a size of 7×7 cm and a molecular weight cutoff of 100 KDa as base membranes for subsequent use;
[0090] S43, immersing the membrane in the aqueous solution for 5 minutes, taking it out, and air-drying it until the membrane surface is dry;
[0091] S44, the membrane after the water phase is dried is further placed into the organic phase solution for interfacial polymerization reaction, taken out after 60 seconds, and air-dried until the membrane surface is dry;
[0092] S45. The dried membrane is placed in a 60°C constant temperature drying oven for heat curing. After 60 seconds, a nanofiltration membrane is obtained. The dried high-selectivity nanofiltration membrane is taken out and sealed in a water environment for subsequent measurements.
[0093] S46. Take out the dried nanofiltration membrane, pre-press it at a pressure of 0.6 MPa for 30 minutes, and then test the performance of the prepared highly selective nanofiltration membrane using pure water, 2000 ppm Na2SO4 aqueous solution, 2000 ppm MgSO4 aqueous solution, 2000 ppm MgCl2 aqueous solution and 2000 ppm NaCl aqueous solution at a pressure of 0.2 MPa.
[0094] The test results show that the pure water permeability of the highly selective nanofiltration membrane is 19.36 L·m -2 ·h -1 bar -1 The retention rate of Na2SO4 aqueous solution is 95.33%, the retention rate of MgSO4 aqueous solution is 84.51%, the retention rate of MgCl2 aqueous solution is 62.44%, and the retention rate of NaCl aqueous solution is 18.79%.
[0095] in conclusion:
[0096] The high-selectivity nanofiltration membranes prepared in Examples 1 to 3 of the present invention have significantly higher rejection rates for different inorganic salt ions than the nanofiltration membranes prepared in Comparative Examples 1 to 3 under the corresponding scenarios, and significantly higher selectivity than the nanofiltration membrane without adding two-dimensional materials (Comparative Example 4); at the same time, the permeability of the nanofiltration membranes prepared in Examples 1 to 3 is basically the same as the performance level of the nanofiltration membranes prepared in Comparative Examples 1 to 3 under the corresponding scenarios, and significantly higher than the permeability of the nanofiltration membrane without adding two-dimensional materials (Comparative Example 4). Therefore, the nanofiltration membrane prepared by the method for preparing a high-selectivity nanofiltration membrane provided by the present invention has a very good effect.
[0097] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a highly selective nanofiltration membrane based on functionalized two-dimensional materials, characterized in that: include: Step 1, exfoliating and freeze-drying the chemically grafted carboxylated molybdenum disulfide powder to obtain carboxylated molybdenum disulfide nanosheets; The carboxylated molybdenum disulfide nanosheets are prepared into an aqueous solution of a preset concentration, and the solution is stirred to form a material dispersion; Step 2, using piperazine as an aqueous phase monomer to prepare an aqueous solution as an aqueous phase solution; using n-hexane as a solvent and trimesoyl chloride as an organic phase solute to prepare a mixed solution as an organic phase solution; Step 3, select a polyethersulfone ultrafiltration membrane as a base membrane, immerse the base membrane in the material dispersion liquid, take it out and place it in a culture dish covered with absorbent paper, perform a uniform dispersion treatment and then dry the surface; Step 4: After the membrane surface is dried, it is immersed in an aqueous solution, taken out and air-dried, and then immersed in an organic solution, taken out again and air-dried, and then heat-cured to obtain a composite nanofiltration membrane with high surface charge density and high selectivity.
2. The method for preparing a highly selective nanofiltration membrane according to claim 1, characterized in that: In step 1, the chemical grafting method of the carboxylated molybdenum disulfide powder is a hydrothermal synthesis method, and the reagents used are sodium molybdate, thiourea and thioglycolic acid. The hydrothermal synthesis is carried out at a concentration ratio of 1:2:0.05 at 200-240°C for 30-48 hours to obtain a carboxylated molybdenum disulfide aqueous solution.
3. The method for preparing a highly selective nanofiltration membrane according to claim 1, characterized in that: In the step 1, exfoliation refers to ultrasonic dispersion and exfoliation of the carboxylated molybdenum disulfide aqueous solution obtained by hydrothermal synthesis using an ultrasonic cell disruptor to obtain carboxylated molybdenum disulfide nanosheets uniformly dispersed in water, and the ultrasonic conditions are: ultrasonic frequency of 60-80KHz, time of 3-6h, and temperature of 25-30°C.
4. The method for preparing a highly selective nanofiltration membrane according to claim 1, characterized in that: In step 1, freeze drying refers to freeze drying the peeled carboxylated molybdenum disulfide nanosheet aqueous solution using a freeze dryer to obtain dry carboxylated molybdenum disulfide nanosheet solid powder. The freeze drying conditions are: air pressure less than 15 Pa, temperature less than -60°C, and time for 36-48 hours.
5. The method for preparing a highly selective nanofiltration membrane according to claim 1, characterized in that: In step 1, The concentration of carboxylated molybdenum disulfide in the aqueous solution of the preset concentration is 100-300 mg / L; Before use, a magnetic stirrer is used to stir and disperse the prepared aqueous solution of a preset concentration. The stirring conditions are: the speed of the magnetic stirrer is 800-1200 rpm, and the stirring time is 30-60 min.
6. The method for preparing a highly selective nanofiltration membrane according to claim 1, characterized in that: In step 2, the concentration of piperazine in the aqueous phase solution is 0.1-0.25 wv%, and the concentration of trimesoyl chloride in the organic phase solution is 0.05-0.15 wv%.
7. The method for preparing a highly selective nanofiltration membrane according to claim 1, characterized in that: In step 3, the molecular weight cutoff of the selected bottom membrane is 80-100 KDa.
8. The method for preparing a highly selective nanofiltration membrane according to claim 1, characterized in that: In step 3, the base film is immersed in the material dispersion liquid, and the immersion conditions are: temperature of 23-25° C. and time of 3-10 minutes.
9. The method for preparing a highly selective nanofiltration membrane according to claim 1, characterized in that: In step 3, The uniform dispersion treatment means that the base film taken out from the material dispersion is placed in a culture dish covered with absorbent paper, fixed in the culture dish with a phoenix clip, and then placed flat on a constant temperature shaker for mixing and shaking, so that the material loaded on the surface of the membrane is evenly dispersed on the entire membrane surface. The mixing conditions are: temperature 25-30°C, amplitude 1-5mm, rotation speed 5-10rpm, time 3-5min; Surface drying refers to air drying the membrane surface by means of an electric fan, and the air drying conditions are: the fan power is 25-50W, and the time is 3-5min.
10. The method for preparing a highly selective nanofiltration membrane according to claim 1, characterized in that: In step 4, The conditions for soaking in the aqueous solution are: temperature of 23-25°C, time of 3-10 min; The conditions for immersing in the organic phase solution to complete the interfacial polymerization reaction are: temperature 23-25°C, time 30-60s; Thermal curing treatment means that the membrane taken out from the organic phase solution is air-dried, placed in a clean culture dish, and then placed in an oven for drying. The thermal curing conditions are: temperature of 50-70°C and time of 40-80s.
Citation Information
Cited By
Nanofiltration membrane as well as preparation method and application thereof
CN120305835A
